The Erkânname of Hacı Kırzade Hüseyin Hüsnü Baba - Erdem, Cem; Topuzkanamış, Ersoy (Journal of Alevism-Bektashism Studies, 2014)
Erkânnames are the basic written sources of the faith of Bektashism. They have a considerable place in analysis and determination of faith rituals of Bektashism. Tercümans present the rituals and regulates the social life of tarikat relatives. In this context, perceiving style of life in Bektashism is reflected in these texts and this makes these texts very important.This erkânname is registered in Municipality of İstanbul Atatürk Library with the number of OE. 1056, and it is titled as “Halîl İbrâhîm Baba Dergâh-ı Şerîfi Post-nişîni Tire’nin Hasan … Mahallesinden Hâcı Kırzâde Hüseyin Hüsnî Baba Efendi Hazretlerinin Erkânnâme Sûreti”. It is an erkânname of Hacı Kırzade Hüseyin Hüsnü Halifebaba who was the sheikh of Arappınarı Tekke (Horasanlı Halil İbrahim Baba Zaviyesi). The erkanname is considered that it was copied between the dates 1890-1893. It consists of 40 pages. There is some links at the bottom of the pages but no date at the end of the text. This erkânname is very important because of it’s examining the rituals of ikrar cemi. At the end of the text there is some tercümans (prays) and records.
Keywords: Erkânname; Arappınarı Tekkesi; Hüseyin Hüsnü Baba; Bektashism